PENGARUH INTENSITAS PERSEDIAAN DAN FAKTOR-FAKTOR LAINNYA TERHADAP AGRESIVITAS PAJAK PERUSAHAAN MANUFAKTUR DI BEI - Edric Prawiro; Fung Njit Tjhai (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this study is to provide empirical evidence about the factors that affect tax aggressiveness. The factors are current ratio, profitability, inventory intensity, related third party, size, independent commissioner, and leverage. This study uses purposive sampling method which resulted in research samples of 231 manufacture companies listed on Indonesia Stock Exchange during the period of 2018-2020. The data obtained from these samples were analyzed using multiple regression analysis on SPSS 25. that size have influence to tax aggressiveness, whereas current ratio, profitability, inventory intensity, related third party, independent commissioner, and leverage do not have influence to tax aggressiveness.